223 - SEXUALITY, GENDER AND EDUCATION IN THE ADOLESCENCE: THE SEEN SCHOOL AS SUSTENTATION PILLAR (Fiep Bulletin - online, 2011)
The present work has for objective to present the responsibility that falls again on the school into what it says respect to the excess of information distorted for the media referring to the sexuality in the adolescence, as well as, for the question to have diverse cases where the family omits and/or imposes values when approaching this thematic one. It is of great importance that in the quarrels that if the orientation relates sexual, is reflected that the sexuality is basic dimension in the life of the human being and has as characteristic the practical ones and desires related to the pleasure, the affectivity, to the feelings and the exercise of the health and the freedom. The thematic research points that the overload of responsibility trusted to the school is extreme, in which must exert a qualified action in the attendance to the demands of the adolescent public on sexual orientation, however is not given the same one, necessary subsidies, as: professional qualification, pedagogical increase of the cash of able professionals and didactic resources this work to conquer its effectiveness.
Keywords: sexuality; adolescence; family; media; education